2010
DOI: 10.1007/s12224-010-9094-1
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the Karyological Knowledge of Mediterranean Romulea Species (Iridaceae)

Abstract: Eighteen chromosome counts are reported in nine Mediterranean Romulea species. Among them, four species have a wide distribution range (R. bulbocodium, R. columnae, R. ramiflora and R. rollii) and five are narrow central Mediterranean endemics (R. bocchierii, R. ligustica, R. linaresii, R. requienii and R. revelieri). Chromosome numbers range from 2n=3x=27 in one R. columnae accession to 2n= 6x=54 in R. linaresii. Our results only partially agree with previous reports, and the chromosome number records of R. b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…; Frignani and Iiriti ; Peruzzi et al. ; Karaismailoglu ; Mifsud ), relationships among individual taxa have not been investigated sufficiently, and our knowledge on their ecology, physiology, and evolutionary history is limited (Kök et al. ; Angiolini et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Frignani and Iiriti ; Peruzzi et al. ; Karaismailoglu ; Mifsud ), relationships among individual taxa have not been investigated sufficiently, and our knowledge on their ecology, physiology, and evolutionary history is limited (Kök et al. ; Angiolini et al.…”
Section: Introductionmentioning
confidence: 99%
“…This genus is comprised of about 100 taxa and displays a disjunct distribution pattern, with about 80% of the taxa occurring in southern Africa and on the Arabian Peninsula and the other 20% (about 15 species) occurring in the western parts of the Mediterranean Basin (Goldblatt et al 2008), where they are found in coastal and island ecosystems . While extensive morphological, anatomical, and taxonomical studies on Mediterranean Romulea species already exist (Is ßik and D€ onmez 2007; Coppi et al 2010;Frignani and Iiriti 2011;Peruzzi et al 2011;Karaismailoglu 2015;Mifsud 2015), relationships among individual taxa have not been investigated sufficiently, and our knowledge on their ecology, physiology, and evolutionary history is limited (K€ ok et al 2007;Angiolini et al 2015). Mediterranean Romulea species typically grow in dry or temporarily humid grasslands and pastures mainly comprised of annual species ( Carni et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ixioideae), which includes over 800 species and about 30 genera and is the largest subfamily of Iridaceae (Iş ik and Dönmez, 2007;Kutbay et al, 2001;Özdemir et al, 2011). According to different authors (Béguinot, 1907(Béguinot, , 1909Čarni et al, 2014;Marais, 1980), the genus comprises about 95 species, most of which are found in southern Africa and the Arabian Peninsula (Manning and Goldblatt, 2001); about 15 species can be found in the Mediterranean basin (Peruzzi et al, 2011). The genus Romulea is distinguished from other genera of Iridaceae by its high degree of polymorphism and intraspecific variability (Frignani and Iiriti, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In Italy 12 autochthonous species occur (Frignani and Iiriti, 2011a,b,), that are important components of the Italian flora. Although some studies on Mediterranean species of Romulea have been published (Čarni, 2014;Erol and Küç üker, 2003;Frignani and Iiriti, 2011a,b;Goldblatt et al, 2002;Iş ik and Dönmez, 2007;Kök et al, 2007;Özdemir et al, 2011;Peruzzi et al, 2011;Rita, 1989Rita, -1990, relationships among Euro-Mediterranean taxa have not been sufficiently investigated and many of the entities described are either subordinated to or considered synonyms of Romulea bulbocodium (L.) Sebast. & Mauri http://dx.doi.org/10.1016/j.flora.2015.05.001 0367-2530/© 2015 Elsevier GmbH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation